La planificación tributaria como mecanismo para lograr la eficiencia económica en el tratamiento del impuesto a la renta en las compañías del sector farmacéutico del Ecuador - Sánchez Salazar, María Johanna (2020)
This research studies tax planning as a tool for economic optimization in the treatment of income tax for companies in the pharmaceutical sector of Ecuador, is aimed at limited liability companies that are dedicated to the distribution of drugs in the country since they contribute to the economic growth of the country and to the strengthening of the health system. The research was carried out using a qualitative and quantitative approach. A referential guide to tax planning was developed based on legal regulations, the theoretical foundations of tax planning (objectives, principles, scope, stages of tax planning and the legal limits for its application), the analysis of empirical studies carried out on different economic sectors and financial tools for evaluating tax planning; in order to know how it influences the determination and settlement of income tax. The results obtained concluded that tax planning influences in a positive way the companies in the pharmaceutical sector, allowing to propose alternatives that help them generate economic efficiency in the treatment of income tax; directing companies towards optimal scenarios, with a higher probability of success and less implicit risk; as well as the timely fulfillment of tax obligations; and, promoting taxpayers to ethical compliance with legal regulations, avoiding falling into such as tax evasion.